Investigation of the behavior of the atmospheric dynamics during occurrences of the ozone hole's secondary effect in southern Brazil - G. D. Bittencourt; D. K. Pinheiro; J. V. Bageston; H. Bencherif; L. A. Steffenel; L. Vaz Peres (Annales Geophysicae, 2019)
The Antarctic ozone hole (AOH) directly influences the Antarctic region, where its levels can reach values below 220 DU. The temporary depletion of ozone in Antarctica generally occurs between the beginning and middle of August, during the austral spring, and extends to November, when a temporary reduction in ozone content is observed in a large region over the Antarctic continent. However, masses of ozone-depleted air can break away from the ozone hole and reach mid-latitude regions in a phenomenon known as the secondary effect of the Antarctic ozone hole. The objective of this paper is to show how atmospheric dynamics behave during the occurrence of this type of event, especially in mid-latitude regions, such as southern Brazil, over a 12-year observation period. For the analysis and identification of the events of influence of the AOH on the southern region of Brazil, data from the total ozone column were used from ground-based and satellite experiments, the Brewer Spectrophotometer (MkIII no. 167), and the Ozone Monitoring Instrument (OMI) on the Aura satellite. For the analysis of the stratospheric and tropospheric fields, the ECMWF reanalysis products were used. Thus, 37 events of influence of the AOH that reached the southern region of Brazil were identified for the study period (2006–2017), where the events showed that in approximately 70 % of the cases they occurred after the passage of frontal systems and/or atmospheric blocks over southern Brazil. In addition, the statistical analysis showed a strong influence of the jet stream on mid-latitude regions during the events. Among the 37 identified events, 92 % occurred in the presence of the subtropical and/or polar jet stream over the region of study, possibly explaining the exchange of air masses of ozone deficient in the upper troposphere–lower stratosphere (UT–LS) region.